DNA barcoding, microarrays and next generation sequencing: recent tools for genetic diversity estimation and authentication of medicinal plants. (3rd March 2016) - Sarwat, Maryam; Yamdagni, Manu Mayank
Abstract: DNA barcoding, microarray technology and next generation sequencing have emerged as promising tools for the elucidation of plant genetic diversity and its conservation. They are proving to be immensely helpful in authenticating the useful medicinal plants for herbal drug preparations. These newer versions of molecular markers utilize short genetic markers in the genome to characterize the organism to a particular species. This has the potential not only to classify the known and yet unknown species but also has a promising future to link the medicinally important plants according to their properties. The newer trends being followed in DNA chips and barcoding pave the way for a future with many different possibilities. Several of these possibilities might be: characterization of unknown species in a considerably less time than usual, identification of newer medicinal properties possessed by the species and also updating the data of the already existing but unnoticed properties. This can assist us to cure many different diseases and will also generate novel opportunities in medicinal drug delivery and targeting.